VD_FINDINFO Jug / 2020 / 337 vom 28. Februar 2020 - VD Tribunal cantonal (2020)
TENTATIVE SIMPLE, MEURTRE, EXPULSIONDROIT PÉNAL, VIOLENCE CONTRE LES AUTORITÉS, LÉSION CORPORELLE SIMPLE | 22 ad 111 CP, 66a CP